Isotopic evidence for oligotrophication of terrestrial ecosystems. Issue 11 (November 2018) - Craine, Joseph; Elmore, Andrew; Wang, Lixin; Aranibar, Julieta; Bauters, Marijn; Boeckx, Pascal; Crowley, Brooke; Dawes, Melissa; Delzon, Sylvain; Fajardo, Alex; Fang, Yunting; Fujiyoshi, Lei; et al.
Abstract Human societies depend on an Earth system that operates within a constrained range of nutrient availability, yet the recent trajectory of terrestrial nitrogen (N) availability is uncertain. Examining patterns of foliar N concentrations and isotope ratios (δ15 N) from more than 43, 000 samples acquired over 37 years, here we show that foliar N concentration declined by 9% and foliar δ15 N declined by 0.6–1.6‰. Examining patterns across different climate spaces, foliar δ15 N declined across the entire range of mean annual temperature and mean annual precipitation tested. These results suggest declines in N supply relative to plant demand at the global scale. In all, there are now multiple lines of evidence of declining N availability in many unfertilized terrestrial ecosystems, including declines in δ15 N of tree rings and leaves from herbarium samples over the past 75–150 years. These patterns are consistent with the proposed consequences of elevated atmospheric carbon dioxide and longer growing seasons. These declines will limit future terrestrial carbon uptake and increase nutritional stress for herbivores. Foliar nitrogen (N) concentrations and isotope ratios obtained from >43, 000 samples acquired over 37 years suggest global declines in N supply relative to plant demand, consistent with elevated atmospheric carbon dioxide.